2006
DOI: 10.1115/1.2172965
|View full text |Cite
|
Sign up to set email alerts
|

Projectile Driving Band Interactions With Gun Barrels

Abstract: This paper discusses results from a series of trials carried out to determine the effect of the projectile driving band on the stress applied to a 155mm gun barrel during firing. The interference between the driving band and gun barrel can apply significant loads to the barrel and, in extreme cases, lead to premature cracking and failure of the barrel. Strain gage data from firing trials has been used to characterize the external strain from firing different projectiles and charges to identify potential proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Lisov investigated the wear mechanisms of 105-and 155-mm artillery projectiles' rotating bands theoretically and experimentally using variable parameters of internal ballistics [7]. Based on the measured strain of the barrel's exterior surface, Andrews [8] found that high charges generally degrade the rotating band by reducing the load the rotating band applies to the 155 mm gun barrel during firing. The influence of rotating band construction on gun tube loading was investigated experimentally and numerically by Toivola et al [9] and Keinänen et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lisov investigated the wear mechanisms of 105-and 155-mm artillery projectiles' rotating bands theoretically and experimentally using variable parameters of internal ballistics [7]. Based on the measured strain of the barrel's exterior surface, Andrews [8] found that high charges generally degrade the rotating band by reducing the load the rotating band applies to the 155 mm gun barrel during firing. The influence of rotating band construction on gun tube loading was investigated experimentally and numerically by Toivola et al [9] and Keinänen et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…During the course of Stephen's doctoral studies, he came to understand that the mechanical properties of polyethylene he was studying depended on how rapidly it is deformed. So, it made sense to accept a post-doctoral position that John Field offered him to investigate strain-rate effects in a number of different polymers that were being considered as replacement materials for the soft metals used in driving bands that spin up shells as they are accelerated up rifled gun-barrels [55][56][57]. Again, Stephen was very fortunate to be joined by two people John Field had attracted to the group (Peter Pope (Ph.D. 1984 [58]) and Nick Safford (Ph.D. 1988 [59])) who had taken over the miniaturised direct impact Hopkinson bar (3 mm diameter) previously developed by David Gorham [60].…”
Section: Stephen M Walley Research Associate Cavendish Laboratory University Of Cambridge Phd Awarded 1982-erosion Of Polyethylene By Solmentioning
confidence: 99%
“…In addition, methods dealing with moving boundaries for updating the fluid field in the expanding combustion chamber are also critical for an accurate simulation. Considered the complex nonlinear factors, such as nonlinear constitutive relation of materials, transient effects and contacts between the mechanical parts, the mechanical interactions between the projectile and the barrel, which affect the flow of the combustion products in the barrel, were investigated by using experimental methods [19][20][21] and numerical methods [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%